(untitled) (London, 2000)
This is a comprehensive review of congenital hemiplegia for the clinician covering all aspects from etiology and pathology to clinical assessment and management, whether orthopaedic, neurological or psychological. The team of expert international contributors highlight the many quite distinct problems of hemiplegia and review all the current approaches. Probable future developments are also described, especially unilateral hemisphere lesions, a topic currently of great interest to basic science researchers.
Keywords: Hemiplegia,Genetic disorders in children,Hemiplegia,Bệnh liệt nửa người,Bệnh liệt nửa người,Sự rối loạn di truyền trẻ em; Psychology,Child,Tâm lý học,Trẻ em